Prevalence and immunopathologic characteristics of seropositive and seronegative hepatitis B virus-associated membranous nephropathy: a retrospective study of 420 biopsy-proven cases - Haitao Lu; Qianqian Xu; Guming Zou; Hongmei Gao; Yue Yang; Wenge Li; Li Zhuo (Renal Failure, 2024)
Background This retrospective study aims to investigate the prevalence and immunopathologic characteristics of seropositive and seronegative hepatitis B virus-associated membranous nephropathy (HBV-MN).Methods Clinicopathologic and serologic records of 420 patients with histologically confirmed HBV-MN between January 2014 and July 2021 were examined to determine the prevalence of seropositive and seronegative HBV-MN. Serum anti-PLA2R antibody testing was conducted on 280 patients with HBV-associated membranous nephropathy (HBV-MN) from August 2018 to July 2021. Immunopathologic characteristics of HBV-MN patients and anti-PLA2R antibody positivity were analyzed.Results Among 420 pathologically confirmed HBV-MN patients, 230 (54.8%) were seropositive for HBV. The seropositive group exhibited higher blood creatinine values and incidence of liver function abnormalities than the seronegative group (p < .05). Serum anti-PLA2R antibody testing on 280 HBV-MN patients revealed a total positive rate of 44.6%, with the seronegative group showing a significantly higher rate (62.6%) compared to the seropositive group (32.1%) (p < .01). The anti-PLA2R antibody-positive group displayed higher levels of urine protein (p < .05), serum cholesterol (p < .01), and IgG4 subtypes (p < .05) compared to the negative group. Additionally, the positive group had significantly lower levels of serum albumin and IgG than the negative group (p < .01).Conclusions This comprehensive study reveals a significantly higher prevalence of seronegative HBV-MN than previously thought. The blood creatinine values and incidence of liver function abnormalities was higher in the serology-positive group than in the serology-negative group. Notably, the seronegative group displayed a higher positive rate of anti-PLA2R antibodies compared to the seropositive group, indicating distinctive clinical and immunopathologic features.